CO-WORKING SPACE DAN GALERI DI KOTA PONTIANAK (JMARS: Jurnal Mosaik Arsitektur, 2020)
Co-working is a working style that involves creative activities in a collaborative working environment and allows anyone to work, share, socialize, and discuss even if they are not in the same organization or company. The existence of co-working spaces in Pontianak City is arguably still rare, the facilities and atmosphere presented are not like co-working spaces in big cities in Indonesia and abroad. Apart from accommodating start-ups, co-working spaces in Pontianak City also need to accommodate communities in fields related to co-working space users. The provision of galleries can be a place to bring the work of users and the community to life as well as to support collaboration. The application of the concept of space that can stimulate unser behavior is expected to solve common workiplace problems.Recently, the 'creative industry' has been talked about and echoed a lot. There are four very potential subsectors, namely visual communication design, music, video animation, and architecture, most of which are young people. Today's young people tend to want to work according to their wishes without any pressure from anyone. Freelancers and young entrepreneurs are part of creative industry players who are just starting / pioneering their careers and most of them are young people.